The Effects of Intra-Amnionic Feeding of Arginine And/or ß-Hyroxy-ß-Methylbutyrate on Jejunal Gene Expression in the Turkey Embryo and Hatchling - Foye, O.T.; Ashwell, C.; Uni, Z.; Ferket, P.R. (International Journal of Poultry Science, 2009)
In-ovo Feeding (IOF), injecting nutrients into the amnion of the developing embryo may enhance post-hatch growth by enhancing intestinal expression and function prior to hatch. This hypothesis was evaluated with IOF solutions of Arginine (ARG), HMB and Egg White Protein (EW) in turkeys. Four treatments were arranged as a factorial of 2 levels of ARG (0 and 0.7%) and HMB (0 and 0.1%). An IOF solution of EW (18%) was evaluated for contrast. At 23 d of incubation (23E) each IOF solution was injected into the amnion. Upon hatch all poults were fed ad libitum. Intestinal mRNA of the digestion/absorption related genes Sodium Glucose Transporter (SGLT), Peptide transporter (Pept), Sucrase-isomaltase (SI) and Aminopepdiase (AP) were determined at 25E, hatch, 3 and 7 d by real-time PCR analysis. The data was analyzed as a 2X2 factorial and 1-way ANOVA for contrast. There were significant ARG X HMB effects on Pept, SGLT, SI and AP mRNA levels at hatch. IOF HMB alone enhanced Pept, SGLT, SI and AP intestinal mRNA expression at hatch, whereas inclusion of ARG depressed expression. There were main and independent effects of HMB or ARG on mRNA expression of SI and AP at 25E, in which ARG alone depressed expression, while IOF HMB alone had no effect on SI or AP expression. These results suggest that IOF may enhance early growth by improving intestinal capacity to digest and absorb nutrients at hatch which may fuel more rapid post-hatch growth.